Roles of plant growth promoting rhizobacteria in suppression of Ganoderma Basal stem rot in oil palm - Parvin, Waheeda (2014)
The Basal Stem Rot (BSR) disease caused by Ganoderma boninense is a major economic concern and it is a predominant disease of oil palm in Southeast Asia including Malaysia. Until now there is no effective control measure available for this disease. A sustainable control measure is using bio-control agents such as Plant Growth Promoting Rhizobacteria (PGPR). Two PGPR, Pseudomonas aeruginosa UPMP3 and Burkholderia cepacia UPMB3 isolated from oil palm rhizosphere were studied for their potential to be used as biocontrol agents. The objectives of this study were (i) to determine the mechanisms of plant growth promotion and pathogen suppression by P.aeruginosa UPMP3 and B. cepacia UPMB3, (ii) to identify and quantify the antibiotics produced by selected PGPR and to determine their effects on G. boninense mycelial Growth in vitro, and (iii) to evaluate the effects of selected antibiotic application on the development of BSR disease and on the expression of defense related genes during Ganoderma-oil palm interaction. Experiments were conducted to detect phytohomones, antibiotics, siderophores, and volatile substance, hydrogen cyanide (HCN) produced by these two bacterial strains. Various antibiotics produced were identified and quantified using High Performance Liquid Chromatography (HPLC). In vitro bioassay was carried out to determine the effect of antibiotics and volatiles produced on G. boninense. Subsequent experiments were conducted in the glasshouse with the selected antibiotic to evaluate BSR disease development and to detect pathogenesis-related (PR) genes induced during Ganoderma-oil palm interaction at the intervals of 0, 2, 4, 6, and 8 weeks after inoculation. The results showed that P. aeruginosa UPMP3 and B. cepacia UPMB3 produced phytohormones indole-3- acetic acid (IAA), salicylic acid (SA) and zeatin. But only P. aeruginosa UPMP3 produced volatile substance HCN. The results revealed that P. aeruginosa UPMP3 produced various antibiotics: 2,4-diacetylphloroglucinol (2,4-DAPG), phenazine (PHZ), pyocyanin (PYO), phenazine -1- carboxylic acid (PCA), pyoluteorin, phenazine-1-carboxamide (PCN) and pyrrolnitrin, while B. cepacia UPMB3 produced pyocyanin, pyoluteorin and pyrrolnitrin. For in vitro bioassay using antibiotics and volatile substances, it was observed that the inhibition of Ganoderma mycelial radial growth caused by P. aeruginosa UPMP3 and B. cepacia UPMB3 were 94.21% and 21.38% for antibiotics, respectively and 51.16% and 8.89% for volatile substances, respectively after 7 days of incubation. P. aeruginosa UPMP3 was more effective than B. cepacia UPMB3 in suppressing Ganoderma in vitro. Based on these results, P. aeruginosa UPMP3 was selected for further studies. Three antibiotics namely PHZ, PCA and PYO were extracted from P. aeruginosa UPMP3 due to the availability of these standards and quantified using (HPLC). Standards for PHZ, PCA and PYO were completely separated with retention times of 41.590, 39.740 and 34.863 min, respectively. At 250 nm wave length, the bacterial strain produced a maximum concentration of PHZ (1.36 μg/mL) and PCA (9.62 μg/mL). At 262 nm the maximum concentration of PYO was 15.48 μg/mL. For in vitro bioassay, PHZ was more effective than PCA and PYO in suppressing Ganoderma at concentration of 1mg/mL. The inhibition percentages were 100%, 78.61% and 91.87%, respectively. For glasshouse study, 5 treatments were used: T1, Negative control; T2, Positive control; T3, Phenazine (1mg/mL); T4, Phenazine (2mg/mL); T5, Hexaconazole (0.048 mg/mL). Plants in T4 showed the highest disease reduction of 52.76% compared to T5 (25.27%). Two putative pathogenesis-related (PR) genes including chitinase and β-1, 3-glucanase were differentially expressed in oil palm roots with different treatments. Chitinase was expressed constantly throughout the sampling intervals while β-1, 3-glucanase expressed at later intervals. The results of this study showed that the antibiotic phenazine has strong antimicrobial activity against G. boninense in vitro and was comparable to chemical fungicide in suppressing BSR in glasshouse conditions. The antibiotic phenazine extracted from P. aeruginosa UPMP3 could be potentially developed as a commercial formulation to suppress BSR disease of oil palm to reduce the application of harmful pesticides, thus limiting their hazardous effects on the environment.